ANALISIS TINDAK ILOKUSI YANG DILAKUKAN OLEH GSD DALAM VIDEO KENAPA KITA MEMBENCI? - Suci Nurul Afidah; Asep Purwo Yudi Utomo (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2021)
The purpose of this research is to describe the illocutionary acts on one of Gita Savitri Devi’s Youtube Channel video entitled Kenapa kita membenci? Beropini eps. 46. The method use in this research is descriptive qualitative method. The data in this research are illocutionary acts spoken by Gita Savitri Devi in one of her Youtube Channel videos. The data source in this research is the narration delivered by Gita Savitri Devi in that video. The data collection techniques using hearken technique. Data analysis techniques in this research were carried out through the steps : (1) Data transcription, (2) Data classification, and (3) Data inference. The results obtained by the type of assertive illocutionary acts, directive illocutionary acts, and expresive illocutionary acts. While the types of commissive illocutionary acts and declaration illocutionary acts were not found in this research.